A minimally invasive animal model of atherosclerosis and neointimal hyperplasia for translational research - Max L. A. Ebert; Vanessa F. Schmidt; Osman Öcal; Anne von Thaden; Olaf Dietrich; Bastian Popper; Sandra Elges; Max Seidensticker; Jens Ricke; Melanie A. Kimm; Astrid Jeibmann; Moritz Wildgruber (European Radiology Experimental)
Abstract Background A variety of animal models has been developed for research on atherosclerosis and neointimal hyperplasia. While small animal models contain limits for translational research, we aimed to develop an atherosclerosis model with lumen-narrowing plaques to foster basic research in vascular biology, the development of new angioplasty devices, and vessel wall imaging approaches. Methods Endothelial denudation was performed via a minimally invasive approach through the auricular artery, followed by stent-retriever mediated endothelial injury in New Zealand White rabbits (n = 10). Along with a high-fat diet, the rabbits developed lumen-narrowing atherosclerosis and neointimal hyperplasia of the iliac arteries within a 6-week period after mechanical injury. The stent-retriever method was compared with a conventional rabbit model (n = 10) using balloon denudation via surgical access, and both models were analyzed with a particular focus on animal welfare. Fisher’s exact, Mann–Whitney U, and unpaired t-tests were used. Results The average time for the entire procedure was 62 min for the balloon group and 31 min for the stent-retriever group (p < 0.001). The stent-retriever model resulted in less periprocedural morbidity (including expenditure, intubation time, anesthetics, and end-tidal CO2 level) and mortality (40% mortality in the conventional group compared to 0% in the stent-retriever model, p = 0.011), while generating lumen-narrowing atherosclerotic lesions with key features as compared to humans as revealed by time-of-flight magnetic resonance imaging and histology. Conclusion We developed a minimally invasive model of iliac atherosclerosis with high reproducibility and improved animal welfare for translational research. Relevance statement This advanced rabbit model could allow for translational research in atherosclerosis, including pharmacological investigations as well as research on interventional angioplasty procedures. Key Points Rabbit models show similar lipid metabolism as humans. Stent-retriever mediated endothelial denudation causes neointimal hyperplasia and lumen narrowing. This minimal invasive model allows for clinical translation, including pharmacological investigations and vessel wall imaging. Graphical Abstract